Enhanced photocatalytic activity of TiO2 by K incorporation towards acetaldehyde and NO oxidation: The role of K single-ion dopants and additional K-compound structures - Zhao, Shufang; Ji, Yujing; Jeong, Miyeon; Choe, Huicheol; Lee, Jea Won; Kim, Soong Yeon; Saqlain, Shahid; Peng, Zhikun; Liu, Zhongyi; Kim, Young Dok (ELSEVIER SCIENCE SA, 2022)
Various amounts of K were deposited on TiO2 (P25), and the resulting structures were used as photocatalysts for acetaldehyde and NO oxidation. For acetaldehyde under dry and moderately humid conditions, 0.008 wt% of K boosted photocatalytic activity, whereas higher K contents resulted in declined activity. A small amount of K modified the lattice and optical properties of TiO2, resulting in the enhanced photocatalytic activity, whereas excessive K formed separate and less active K-compound structures on the TiO2 surface. In contrast, the photocatalytic activity was gradually decreased with increasing K content for acetaldehyde oxidation under higher humidity conditions, whereas the NO3- selectivity for NO oxidation gradually increased as K content increased. We highlight different roles of K species in TiO2 samples with dissimilar structural properties, and the necessity of fine adjustment of the K content in K-TiO2, depending on the reactions and conditions, to which photocatalysts are applied.